(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The levels of development vary in high degrees from country to another and as well between regions in the same country, So the topic study and analysis the regional divergence in development levels, was the main concern of many planners and decision makers, Study problem focus on regional variance of investment in the industry sector between the Iraq country governorates because it wasn’t dependant on quantitative measures indicate the actual needed to the investment of that sector for each governorate , To exceed this problem we Build Mathematical Model explains the regional variance of investment between governorates through the measure of correlation between studies variables using Factor Analysis model. Measure the impact of the studies variables in the regional distribution for the investment using Ridge Regression Model. The study reached to identified the scale of priorities to distribute the investment in the industry sector between the Iraqi governorates as follow (Al-Muthanna, Missan,Wasit, Salahuddinni, Thi-Qar, Diala, Kerbala, Kirkuk, Al-Qadisiya, Al-Anbar, Al-Najaf, Babil, Nineueh, Basrah,Baghdad ) realized balance regional development .